Integrasi Nilai-Nilai Islami dalam Praktik Kepemimpinan Pendidikan: Membangun Lingkungan Pembelajaran yang Berdaya Saing - Shofiyyah, Nilna Azizatus; Komarudin, Tedy Sutandy; Ulum, Miftahul (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
This research analyzes the integration of Islamic values in educational leadership practices and their impact on a competitive learning environment. A qualitative method with a literature study approach was utilized. The objective was to understand how educational leaders integrate Islamic values into their leadership practices and the resulting effects on the learning environment. The findings indicate that the integration of Islamic values creates a holistic learning environment, fostering students' morality, ethics, and social awareness. Educational leaders who integrate Islamic values serve as inspirational role models and strengthen the connection with students' everyday experiences. Additionally, it helps create an inclusive school culture and promotes collaboration among students. The implications of this research provide an understanding of the importance of integrating Islamic values into educational leadership.